Thyroid cancer: about 60 observations - Gregorio, Luis A (Cirugía del Uruguay, 1974)
Case material of our Institute of Endocrinology consists of a series of 60 thyroid cancers. Frequency of disease, most common symptomatology, clinical appearence and auxiliary elements for diagnosis are described. Special emphasis is laid on the importance attributed to cytological puncture and immunological study or Paseyro's test, is fundamental in a large number of patients in order to obtain a precise diagnosis. In this paper we find a review of pathological anatomy, treatment, surgical tactics, operatory accidents, complications and recurrencies in this series, as well as a summary of those cases in which the author himself intervened.